Fiscal decentralization and urbanization in Indonesia - Margherita Comola; Luiz de Mello (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Indonesia went through a process of fiscal decentralization in 2001 involving the devolution of several policymaking and service delivery functions to the subnational tiers of government (provinces and districts). This process is likely to have affected regional patterns of urbanization, because the new prerogatives granted to the local governments have altered the distribution of urban amenities and labour market outcomes among and within the local jurisdictions. This paper uses a dataset of local governments for 1996 and 2004-05 to estimate the effect of the decentralization of minimum-wage setting in 2001 on urban population growth. Our findings suggest that, controlling for demand- and supply-side determinants of urban population growth, if the minimum wage had risen by an additional 81.5 thousand rupiah (25 per cent of its initial mean value), the urban population would have risen by an additional 0.4 per cent from its initial level.
Keywords: H72; J61; R23; 330; Indonesia; minimum wage; federalism; urbanization